Construction and evaluation of hierarchical structures of indexing languages for online catalogs of libraries: An experience of the Sao Paulo state university - Lopes Fujita, Mariangela Spotti [UNESP]; Moreira, Walter [UNESP]; Dos Piovezan Santos, Luciana Beatriz [UNESP]; Andrade Cruz, Maria Carolina E. [UNESP]; De Barros Ribas, Rosane Rodrigues [UNESP] (IMR Press, 2018)
The construction and updating of indexing languages depend on the organization of their hierarchical structures in order to determine the classification of related terms and, above all, to allow a constant updating of vocabulary, a condition for knowledge evolution. The elaboration of an indexing language for online catalogs of libraries' networks is important considering the diversity and specificity of knowledge areas. From this perspective, the present paper reports on the work of a team of catalogers and researchers engaged in the construction of a hierarchical structure of an indexing language for an online catalog of a university library's network. The work on hierar-chical structures began by defining the categories and subcategories that form the indexing language macrostructure by using the parameters of the Library of Congress Subject Headings, the National Library Terminology and the Vocabulary' of the University of Sao Paulo Library's system. Throughout the stages of the elaboration process of the macrostructure, difficulties and improvements were observed and discussed. The results enabled the assessment of the hierarchical structures of the languages used in the organization of the superordinate and subordinate terms, which has contributed to the systematization of operational procedures contained in an indexing language manual for online catalogs of libraries.
Keywords: Engineering; Hierarchical; Indexing languages; Subject heading lists